YOUTH CHALLENGES IN ACHIEVING FINANCIAL WELL-BEING: THE ROLE OF FINANCIAL SECURITY - Irma Kurniasari; Cicik Retno Wati (MESP–FEB UNS, 2025)
This study aims to examine the relationships between financial behavior, expected future financial security, financial security, and financial well-being. Furthermore, it seeks to determine the role of financial security as a mediator in the relationship between financial behavior and financial well-being, as well as between expected future financial security and financial well-being. This quantitative research collected data through the distribution of an online questionnaire. The study was conducted on individuals from Generation Z and Millennials in Surabaya, Indonesia, who invest in banking financial products or capital market financial products. The sampling technique used was purposive sampling, with a sample size of 100 respondents who met the study's criteria. The results indicate that an individual's financial behavior can lead to improved well-being. Furthermore, financial security serves as a crucial bridge in this relationship. The sense of safety and capability formed from preparing an emergency fund, maintaining regular financial control, remaining consistent with goals, and being free from debt burdens are pivotal in achieving greater financial well-being, more so than relying on financial behavior alone. This study also found that the expectation of future financial security (expected future financial security) does not directly determine an individual's level of financial well-being. However, the findings confirm that financial security acts as a primary catalyst, mediating the relationship between expected future financial security and financial well-being.